2017
DOI: 10.1093/bja/aew396
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care utilization and outcomes after high-risk surgery in Scotland: a population-based cohort study

Abstract: UKCRN registry no. 15761.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 22 publications
(20 reference statements)
5
59
1
Order By: Relevance
“…However, these values were not censored in the linear regression model used to estimate the association whilst high-risk patient groups undergoing non-cardiac surgery are often not provided with this level of care despite a much higher mortality rate [8,11,12]. Overall rates of postoperative admission to critical care remain low, even amongst high-risk patients [8][9][10]. The findings of an analysis of a large US Medicare dataset exploring the association between mortality, length of hospital stay, and healthcare costs with critical care admission for patients over 65 years of age undergoing one of five major surgical procedures did not identify any benefit of critical care admission [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these values were not censored in the linear regression model used to estimate the association whilst high-risk patient groups undergoing non-cardiac surgery are often not provided with this level of care despite a much higher mortality rate [8,11,12]. Overall rates of postoperative admission to critical care remain low, even amongst high-risk patients [8][9][10]. The findings of an analysis of a large US Medicare dataset exploring the association between mortality, length of hospital stay, and healthcare costs with critical care admission for patients over 65 years of age undergoing one of five major surgical procedures did not identify any benefit of critical care admission [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates from high income countries suggest that postoperative complications occur in up to 20% of patients [6,7], and short-term mortality may vary from 1 to 4% [8][9][10][11][12][13][14][15][16]. While effective perioperative care is considered essential to the safe provision of surgical treatments [17], the optimal level of such care has not been defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Unplanned admissions to critical care represented a small but important minority (n¼86) and were associated with worse survival outcomes than planned admissions, as previously reported. 7,10,28 The European Surgical Outcomes Study 2 identified that 73% of inpatient deaths were never admitted to critical care after operation, with 43% of those who died having been discharged from critical care; the authors highlighted a systematic failure in allocation of critical care resources. Unplanned admission to critical care can be because of an acute deterioration in an existing clinical condition (potentially preventable), or a serious, unexpected adverse event with a non-modifiable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the value of routine ICU admission after elective surgery has been questioned, given its costs and the lack of robust evidence supporting it [3,4]. Moreover, identification of patients at highest risk, who might benefit from ICU admission, remains a major challenge leading to unacceptable inequity in resource distribution [5].…”
mentioning
confidence: 99%